DNA degradation in human teeth exposed to thermal stress - Lozano Peral, Diego; Rubio-Lamia, Leticia Olga; Santos-Amaya, Ignacio Miguel; Gaitán, María Jesús; Viguera-Mínguez, Enrique; Martín-de-las-Heras, Stella (My University, 2021)
Human identification from burned remains poses a challenge to forensic laboratories, and DNA profiling is widely used for this purpose. Our aim was to evaluate the effect of temperature on DNA degradation in human teeth. Thirty teeth were exposed to temperatures of 100, 200, or 400 °C for 60 min. DNA was quantified by Real-Time qPCR (Quantifiler Human DNA Quantification Kit) and fluorescence spectroscopy (Qubit 3.0 Fluorometer). DNA degradation was evaluated by using STR markers (AmpFLSTR Identifiler Plus PCR Amplification Kit) to determine the allele and locus dropout, inter-locus balance, and degradation slope (observed (Oa) to expected (Ea) locus peak height ratio against the molecular weight). Most of the genomic DNA was degraded between 100 °C and 200 °C. At 100 °C, locus dropout ratios showed significant differences between the largest loci (FGA, D7S820, D18S51, D16S539, D2S1338 and CSF1PO) and amelogenin. Inter-locus balance values significantly differed between all dye channels except between NED and PET. The dropout ratio between D18S51 (NED) and amelogenin (PET) can be recommended for the evaluation of DNA degradation. The Oa/Ea regression model can predict locus peak heights in DNA degradation (R2 = 0.7881). These findings may be useful to assess the reliability of DNA typing for human identification in teeth subjected to prolonged incineration.
Keywords: Criminalística; Forensic DNA; DNA quantification; DNA degradation; STR profiling; Human identification; Burned teeth